Timing matters: lipid intake and its influence on menopausal-related symptoms - Ludovica Verde; Luigi Barrea; Evelyn Frias-Toral; Raynier Zambrano-Villacres; Daniel Simancas-Racines; Pasqualina Memoli; Martina Galasso; Silvia Savastano; Annamaria Colao; Giovanna Muscogiuri (Journal of Translational Medicine)
Abstract Background Menopause contributes to central obesity and increases cardiovascular risk in women. Diet influences both menopausal symptoms and cardiovascular health, but the impact of chrononutrition, namely food timing, is not well understood. This cross-sectional study investigated whether the timing of food intake affected menopausal symptoms in 100 postmenopausal women with overweight or obesity. Methods Anthropometric and clinical parameters, and lifestyle habits were assessed. Menopausal symptoms were evaluated using the Menopause Rating Scale (MRS). Nutritional assessment utilized 7-day food records. Food intake was divided into morning intake (meals from breakfast to lunch) and evening intake (meals from afternoon snacks to dinner). Results The mean MRS score was 22.7 ± 7.8, showing a high prevalence of symptoms in the study population. Postmenopausal women under the median of morning energy intake showed a significantly a higher score for heart discomfort (p = 0.045), while those under the median of morning intake of lipids showed significantly higher scores for heart discomfort and lower scores for bladder problems (p = 0.013 and p = 0.040, respectively). Postmenopausal women above the median evening intake of lipids showed a significantly higher score for heart discomfort (p = 0.007). The heart discomfort score correlated negatively and positively with the morning (r = -0.210, p = 0.034) and evening (r = 0.210, p = 0.034) intakes of lipids, respectively, even after correction for confounding factors (r = -0.219 and r = 0.219, p = 0.028 for both). Conclusion Consuming most of the energy and lipids later in the day was linked to higher prevalence of menopausal symptoms in postmenopausal women with overweight or obesity. This eating pattern may potentially have adverse effects on the cardiovascular health of these women. Therefore, adopting chrononutrition behaviors, particularly favoring an earlier intake of energy and lipids, could prove beneficial as an additional measure in the nutritional therapy for postmenopausal women dealing with overweight or obesity.